The second species of Neowuia Li & Murányi, 2017 (Plecoptera: Perlodidae) from Fujian, China - Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2023)
The second species of Neowuia Li & Murányi, 2017, N. wuyishana sp. nov., is proposed with a description from Mount Wuyi, Fujian Province, southeastern China. Morphological features, namely adults and eggs, support Neowuia as a member of the tribe Diploperlini. Geographically, our study firstly reports the distribution of all Diploperlini in the Oriental region, while Neowuia is the second genus of subfamily Perlodinae recorded in southeastern coastal China.